Effect of Alfacalcidol on multiple sclerosis-related fatigue: A randomized, double-blind placebo-controlled study. (May 2015) - Achiron, Anat; Givon, Uri; Magalashvili, David; Dolev, Mark; Liraz Zaltzman, Sigal; Kalron, Alon; Stern, Yael; Mazor, Zeev; Ladkani, David; Barak, Yoram
Context: Fatigue is one of the most common and disabling symptoms of multiple sclerosis (MS); however, there is no medication that has been approved specifically to treat MS-related fatigue. Objective: We aimed to evaluate the effect of vitamin D analogue, Alfacalcidol, on MS-related fatigue. Design, settings, participants: This was a randomized, double-blind, parallel group, placebo-controlled trial in patients with clinically definite MS by McDonald criteria conducted in a single university-affiliated medical center in Israel. Randomly selected patients from the Sheba MS Registry computerized database ( N =600) were assessed using the self-report Fatigue Severity Scale (FSS). Patients with clinically meaningful fatigue ( N =259) were further assessed for trial eligibility, and MS patients with significant fatigue ( N =158; 61%, 118 females, mean age 41.1 ± 9.2 years and mean disease duration of 6.2 ± 5.5 years) were included in the study and randomized to receive treatment or placebo. Intervention: Alfacalcidol (1 mcg/d, N =80) or placebo ( N =78) was administered for six consecutive months. Main outcome measure: The primary endpoint of the study was the change between Alfacalcidol and placebo-treated patients in the Fatigue Impact Scale (FIS) score; the cut-off point for improvement was defined as 30% decrease. All analyses followed the intention-to-treat principle and were performed for all participants based on the group they were randomly allocated regardless of whether or not they dropped out. Results: Alfacalcidol decreased the mean relative FIS score as compared with placebo (–41.6% vs. –27.4%, p =0.007, respectively). This advantage was further emphasized when the modified FIS (MFIS) relative change was calculated. Quality of Life (QoL) improved in Alfacalcidol-treated patients as compared with placebo in the RAYS psychological ( p =0.033) and social ( p =0.043) sub-scales. The Alfacalcidol-treated group had reduced number of relapses ( p =0.006) and higher proportion of relapse-free patients ( p =0.007). Reduction of relapses by Alfacalcidol became significant at 4 months of treatment, was sustained at 6 months and decayed 2 months after drug discontinuation. Alfacalcidol treatment was safe and no serious adverse events were recorded. Conclusion: Alfacalcidol is a safe and effective treatment strategy to decrease fatigue and improve QoL in patients with MS.